30th AIAA Applied Aerodynamics Conference 2012
DOI: 10.2514/6.2012-2775
|View full text |Cite
|
Sign up to set email alerts
|

CFD Based Study of Unconventional Aeroengine Exhaust Systems

Abstract: The effect of upstream duct curvature on the exhaust plume of a jet engine is currently undocumented. Here, three different upstream curvatures are simulated using CFD to investigate the effect of upstream duct curvature on the over-expanded exhaust plume emanating from a rectangular nozzle of aspect ratio 5.8:1 at a nozzle pressure ratio of 2.5 and Reynolds number of 7.61 × 10 5 . Due to the lack of available experimental data for curved ducts connected to high speed jets, the initial work was to validate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Components with S-shaped features are widely used in aeroengines, for example, inlet particle separator, S-shaped diffuser, compressor transition duct, intermediate turbine duct, and S-shaped nozzle. [1][2][3][4][5] Large curvature characteristics are located in such S-shaped ducts, and complex internal flow characteristics would be induced due to the existence of curvature, and then the performances of such components can be influenced. To design high-performance components with large curvatures, it is necessary to explore the mechanism of compressible flow features in such curved ducts.…”
Section: Introductionmentioning
confidence: 99%
“…Components with S-shaped features are widely used in aeroengines, for example, inlet particle separator, S-shaped diffuser, compressor transition duct, intermediate turbine duct, and S-shaped nozzle. [1][2][3][4][5] Large curvature characteristics are located in such S-shaped ducts, and complex internal flow characteristics would be induced due to the existence of curvature, and then the performances of such components can be influenced. To design high-performance components with large curvatures, it is necessary to explore the mechanism of compressible flow features in such curved ducts.…”
Section: Introductionmentioning
confidence: 99%
“…14 These geometric design parameters definitely have important impacts on the characteristics of flow, IR, and RCS of the serpentine nozzle. Coates and Page 15 conducted the study of unconventional aero-engine exhaust systems, where a contracting S-bend duct was combined with a divergent nozzle. Three different upstream S-duct curvatures were considered, and results showed that the increasing upstream duct curvature reduced the potential core length, but increased losses in the upstream duct.…”
Section: Introductionmentioning
confidence: 99%
“…1 The simulations were run using four different turbulence models. The Rolls Royce Hydra code (version 6.2.16) was used for the Spalart-Allmaras, k-and k-ω SST turbulence models whilst the ANSYS Fluent code was used for the Reynolds-Stress second order turbulence model.…”
Section: Iiic Comparison Of Cfd Methods For An S-bend Duct Of 13d mentioning
confidence: 99%